THE UNCONSCIOUS IN TEACHER/STUDENT INTERACTION: AN APPROACH FROM A PSYCHOANALYTIC PERSPECTIVE - Machado dos Santos , Adelcio; André Escher, Alisson; Martins Leffer, Danielle (Revista Gênero e Interdisciplinaridade, 2025)
In the contemporary context, marked by accelerated social transformations, growing cultural diversity and unprecedented challenges for the educational field, it becomes increasingly urgent to reflect on the subjective dynamics present in school institutions. The aim of this study is to investigate the manifestations of the unconscious in the relationship between teacher and student in light of psychoanalytic theory. This is a qualitative literature review of works by Sigmund Freud and Jacques Lacan, contemporary productions, and 18 articles and dissertations published in the Scientific Electronic Library Online and Google Scholar between 2006 and 2025. The results indicate that the pedagogical relationship is permeated by feelings, fantasies, and unconscious identifications that directly impact the school experience. Psychoanalysis and education are areas of knowledge that dialogue with each other. The teacher needs to listen to the student and develop pleasurable learning actions that boost learning. Sensitive and ethical listening welcomes the student’s uniqueness and recognizes unconscious movements in school. It is concluded that the integration between Psychoanalysis and Education can enrich teacher training and promote more humanized and inclusive pedagogical practices, centered on the recognition of the subject as an agent of desire and language.